Encapsulation of ritonavir in solid lipid nanoparticles: in-vitro anti-HIV-1 activity using lentiviral particles. (4th May 2017) - Javan, Farzaneh; Vatanara, Alireza; Azadmanesh, Kayhan; Nabi-Meibodi, Mohsen; shakouri, Mehdi
Abstract: Objectives: In this study, ritonavir was entrapped into solid lipid nanoparticles (SLNs) employing two production methods. The prepared SLNs were characterized and antiretroviral activity was investigated for more efficient formulation. Methods: Ritonavir-loaded SLNs were produced by solvent emulsification evaporation (SE) and double emulsion methods (DE), and the effects of Tween80 and poloxamer188 as external phase surfactant were compared. Prepared SLNs were characterized in terms of size, surface charge, entrapment efficiency (EE), release profile and thermal behaviour. Moreover, the activity of drug-loaded SLNs was investigated on the lentiviral-based pseudo-HIV-1 particles. Key findings: The average size of negatively charged SLNs was 170–250 nm with polydispersity index (PDI) of 0.2. The most EE% was about 53.2% achieved by DE method in the presence of poloxamer188. It was found that addition of poloxamer188 in the process led to increased entrapment efficiency and particle size. The in-vitro antiviral experiment showed ritonavir SLNs can actively maintain inhibition of virus production as well as free drug. Conclusions: In this study, we showed the SLNs not only can encapsulate ritonavir efficiently but also can maintain its antiviral activity and modulate drug release as promising nanocarrier.